The psychostimulant abuse to improve cognitive enhancement in healthy students (Research, Society and Development, 2023)
The increased use of psychostimulants by healthy students has raised questions about their effects on increasing academic performance. With this, the present study aimed to carry out an integrative review on the effectiveness of these drugs in increasing academic performance in healthy people. Directed with the help of descriptors verified in Health Sciences Descriptors (DECS) and Medical Subject Headings (MESH) according to each database. For the production of the article, searches were carried out in the following databases: Scientific Electronic Library Online (SCIELO), Virtual Health Library (BVS), Web of Science, National Library of Medicine - National Institutes of Health (PUBMED). The following were selected as inclusion criteria: answering the target question and being written in Portuguese or English. As a result, 13 studies were obtained. After analysis, a study was observed that gathered online research data to document the perceived academic benefit of NPS and its relationship with such practice (nonmedical use of prescription stimulants), in which 28.6 % of users agreed that NPS could improve academic performance, and another 38.0% were not sure. It was also noted that drinking and cannabis consumption patterns were more associated with NPS. In addition, the use of methylphenidate was associated with improvement in long-term memory, however, the results were conflicting. Thus, it is necessary to follow up on new research, aiming to intensify the dissemination of information about the risks of self-medication and to promote actions focused on the academical mental health.